Effect of some edaphic conditions on physicochemical and physiological characteristics of ‘Horvin’ plum fruit - Orjuela-Angulo, Mayerlin; Dussán-Sarria, Saúl; Camacho-Tamayo, Jesús Hernán (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Edaphic conditions are determinant factors of fruit quality at harvest. The objective was to establish which edaphic variables influence fruit harvest and to determine the influence of these variables on some physicochemical and physiological characteristics of ‘Horvin’ plum fruits at harvest. In the municipality of Nuevo Colon (Boyaca, Colombia), records of two harvests were made in four locations during 2015 and 2016. Ten trees per row and twenty trees per location were marked, for a total of 80 trees for the four locations. For the chemical soil analyses, four samples were taken per location at a depth between 20 and 30 cm, for a total of 16 soil samples. For the physical analysis, 6 samples were taken per location at a depth between 20 and 30 cm, for a total of 24 soil samples. The results showed that the bulk density in the four locations was high, which is evidence of high levels of compaction in each location, resulting in low fruit development at harvest. A relationship was found with fruits at harvest in characteristics such as weight and diameter for some chemical variables, such as pH, phosphorus, cation exchange capacity, calcium, magnesium, potassium, zinc, copper, boron and sulfur.